2018
DOI: 10.1111/nmo.13346
|View full text |Cite
|
Sign up to set email alerts
|

INPP4B overexpression and c‐KIT downregulation in human achalasia

Abstract: The identification of altered gene expression, including INPP4B, a regulator of the Akt pathway, highlights novel signaling pathways involved in the neuronal and ICC changes underlying primary achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…INPP4B overexpression is associated with human achalasia, which is a rare motility disorder characterized by myenteric neuron and interstitial cells of Cajal abnormalities 82 . Depleting INPP4B by in utero electroporation in mice suppressed medially directed callosal axon formation and significantly attenuated the formation of pyramidal neurons and axon polarization in cortical neurons during cortical development 83 .…”
Section: Discussionmentioning
confidence: 99%
“…INPP4B overexpression is associated with human achalasia, which is a rare motility disorder characterized by myenteric neuron and interstitial cells of Cajal abnormalities 82 . Depleting INPP4B by in utero electroporation in mice suppressed medially directed callosal axon formation and significantly attenuated the formation of pyramidal neurons and axon polarization in cortical neurons during cortical development 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative manometry taught us how to abolish the lower esophageal sphincter to “cure” dysphagia and also how to tailor the Dor fundoplication, to be effective in preventing postmyotomy GERD,23–26 but not be obstructive. Dysphagia is the only clinical consequence of the irreversible damage of myenteric neurons and interstitial cells of Cajal, leading to deranged/absent peristalsis and lack of relaxation of the lower esophageal sphincter disease43; its disappearance leads us to consider the disease as “cured.” Intraoperative manometry indicated that the manometric 0 corresponding to the total abolition of the Lower Esophago-Gastric Sphincter is achieved only after: (1) the complete separation of the U and sling fibers far down (at least for 3 cm) the angle of His; (2) the limited (5–6 cm) upward extension of the myotomy, not to surpass the apex of the hiatus, so to allow a convenient stitch between the apex of the myotomy and the Dor fundoplication; (3) the meticulous section of every thin muscular bridge between the 2 edges of the myotomy. Intraoperative manometry equally taught us to perform the Dor fundoplication with the following technical characteristics: (1) it must be totally abdominal, at least 7 to 8 cm long (5 esophageal+3 gastric myotomy); (2) sutures between the fundus and the 2 edges of the myotomy are applied 1 cm apart, and at least the top 4 are placed fundus-myotomy edge-hiatus; the final Dor pressure is higher if the short gastric vessels are not divided.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated various inflammatory cells infiltrated in LES, such as T cells, eosinophils, and mast cells [2][3][4] . Whole-exome and RNA sequencing of achalasia patients identified achalasia-associated loci enriched for immunological and neurological processes 5,6 , suggesting that the immune response may be a critical factor in the disease. However, most studies have focused on the proportion of immune cells and inflammatory mediators without exploring the underlying mechanism.…”
mentioning
confidence: 99%